Shape model-based semi-automatic morphometric assessment of vertebral deformities in clinical practice - Möller, G.; Andresen, R.; Banzer, D. (Osteologie, 2011)
The accurate and clear reporting of vertebral fractures in routine clinical practice is essential to ensure that patients with osteoporosis receive appropriate treatment to prevent the occurrence of further fractures. A statistical shape model-based vision system for semi-automated morphometry called MorphoXpress® has been developed and needs to be tested in routine clinical practice.This multi-centre medical practice evaluation pilot study compared the degree of agreement between two methods to detect vertebral body deformities in routine clinical practice: qualitative visual evaluation of conventional lateral thoracic and lumbar spine radiographs as a “gold standard” and the MorphoXpress® semi-automatic software system for vertebral morphometry.This pilot study was performed in seven participating osteo-centers in Germany. The analysis included 223 ambulatory patients with 446 conventional lateral thoracic (n = 223) and lumbar (n = 223) spine radiographs showing 2676 vertebrae from T5 to L4. Qualitative visual radiograph evaluation was performed by clinician experts, who classified vertebral shape as fractured or not fractured. MorphoXpress® was used for quantitative assessment of vertebral height in digitized radiographs by localising all morphometric points within the set range of vertebrae based on a statistical model-based vision system. Using the interactive tools in Morpho Xpress→, clinicians could refine the positions of morphometric points to their satisfaction. Agreement between the two methods was analyzed.Using qualitative visual radiograph evaluation, clinicians recognised fractures in 92 (41.3 %) patients while quantitative evaluation with MorphoXpress®with interactive manual corrections detected fractures in 85 (38.1 %) patients. Distribution of fractures was comparable using the two methods. The Morpho Xpress→ system alone identified 76 % of the fractured vertebrae correctly. This result was improved to 98 % using additional manual corrections by the clinician once. The overall mean time needed for MorphoXpress® fracture morphometric assessment of vertebral fractures in clinical practice took 13 minutes and 36 seconds.Quantitative measurement using the current version of the MorphoXpress® software system for vertebral morphometry in combination with qualitative interactive corrections by clinicians seems to be a valuable tool for assessment and follow-up documentation of osteoporotic vertebral deformities in patients without severe scoliosis in epidemiological studies and clinical drug trials only. Currently the technique is too timeconsuming and only after significant improvement of the procedure time and following appropriate training for physicians, MorphoXpress® vertebral morphometry could be a valuable tool in daily routine clinical use for osteoporotic patients.
Keywords: Vertebral fracture; spine; osteoporosis; digital computerised vertebral morphometry